2017
DOI: 10.1159/000481241
|View full text |Cite
|
Sign up to set email alerts
|

Hand-Foot Syndrome and Post-Progression Treatment Are the Good Predictors of Better Survival in Advanced Hepatocellular Carcinoma Treated with Sorafenib: A Multicenter Study

Abstract: 87.3-170.7) and the median overall survival (OS) was 392 days (95% CI: 316.0-468.0). The OS of the patients with ChildPugh class A HCC was significantly better than that of the patients with Child-Pugh class B HCC ( p < 0.0001). The survival curves for Child-Pugh class A-5 points and class A-6 points were significantly different, with that for class A-5 points being better ( p < 0.0001). A significant difference was observed between the patients who exhibited HFS and those who did not, with the former exhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…Thus, HFSR should be kept in mind as a commonly occurring AE in patients with a history of that condition during previous SOR and/or REG treatments. HFSR in association with SOR has been reported as a factor predicting a better therapeutic effect of SOR for HCC . Based on these findings, the relationship between HFSR and therapeutic response with LEN treatment should be analyzed in the future.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, HFSR should be kept in mind as a commonly occurring AE in patients with a history of that condition during previous SOR and/or REG treatments. HFSR in association with SOR has been reported as a factor predicting a better therapeutic effect of SOR for HCC . Based on these findings, the relationship between HFSR and therapeutic response with LEN treatment should be analyzed in the future.…”
Section: Discussionmentioning
confidence: 95%
“…HFSR is thought to be a predictor of good therapeutic response in patients receiving LEN treatment as well as those treated with SOR. 30 On the other hand, appetite loss can cause stoppage of LEN and the BMI of patients with that AE was significantly lower (P < 0.001). Porta et al reported that a low dose and treatment discontinuations were correlated with worse survival in renal cell carcinoma patients treated with sunitinib, indicating the importance of maintaining dose intensity.…”
Section: Discussionmentioning
confidence: 96%
“…The frequency of each AE (all grades) in all patients was similar to that of patients with good hepatic function (mALBI 1, 2a), except for HFSR. HFSR is thought to be a predictor of good therapeutic response in patients receiving LEN treatment as well as those treated with SOR . On the other hand, appetite loss can cause stoppage of LEN and the BMI of patients with that AE was significantly lower ( P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Some adverse effects such as HFS are associated with better survival; however, in more vulnerable patients, they can also lead to a greater impact on quality of life [24, 25]. In a meta-analysis of 14 clinical trials, patients taking capecitabine who developed HFS had a longer overall survival than patients who did not develop HFS: 1100 days (95% confidence interval 1007–1200) vs. 691 days, with a hazard ratio of 0.61 (95% confidence interval 0.56–0.66) [24].…”
Section: Discussionmentioning
confidence: 99%